2006
DOI: 10.2332/allergolint.55.379
|View full text |Cite
|
Sign up to set email alerts
|

Omalizumab is Effective and Safe in the Treatment of Japanese Cedar Pollen-induced Seasonal Allergic Rhinitis

Abstract: Omalizumab was effective and safe in the treatment of SAR induced by Japanese cedar pollen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(65 citation statements)
references
References 21 publications
2
59
0
4
Order By: Relevance
“…Therefore, we concluded that the plant sequences with homology to conifers were probably derived from chloroplasts in airborne pollen grains. Seasonal allergic rhinitis (SAR) to Japanese cedar pollen is a major public health problem in Japan (Okubo et al 2006). Pinus pollen allergy has also been reported (Marcos et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we concluded that the plant sequences with homology to conifers were probably derived from chloroplasts in airborne pollen grains. Seasonal allergic rhinitis (SAR) to Japanese cedar pollen is a major public health problem in Japan (Okubo et al 2006). Pinus pollen allergy has also been reported (Marcos et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Among these, omalizumab, a humanized monoclonal antibody that binds circulating IgE and prevents its attachment to high-affinity IgE receptors, is the most extensively studied agent approved for the treatment of severe uncontrolled asthma with perennial sensitizations. However, a growing number of reports indicate its effectiveness in seasonal and perennial AR in adults/adolescents [90][91][92][93][94] and children [95][96][97][98][99]. Targeting the early phase of the allergic cascade could prove a significant allergic march-preventing treatment.…”
Section: Other Interventionsmentioning
confidence: 99%
“…Okubo y cols 19,20 realizaron un estudio ramdomizado, doble ciego controlado con placebo, en 100 pacientes japoneses con historia de RAE moderada-severa a polen de cedro japonés, en dos regiones de Japón (Tokyo y Osaka), entre octubre de 2001 y abril de 2002. Se administró Omalizumab a dosis de 150, 225, 300 ó 375 mg o placebo en forma SC cada 2 o 4 semanas de acuerdo a los niveles basales de IgE total y peso corporal.…”
Section: Estudios En Rinitis Alérgica Estacional (Ras)unclassified